Pengaruh Brand Awareness, Asosiasi Merek, Persepsi Kualitas dan Persepsi Harga Terhadap Keputusan Pembelian Kosmetik Wardah.: - - Farah Almas Fadilah; Arini Hidayah; Naelati Tubastuvi; Totok Haryanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the impact of Brand Awareness, Brand Association, Perceived Quality and Perceived Price on Wardah cosmetic purchasing decisions among the general public in Purwokerto, using non-probability sampling techniques and involving 124 respondents. The research variables include four independent variables, namely the influence of Brand Awareness, Brand Association, Perceived Quality, Perceived Price Qualityice one dependent variable, namely purchasing decisions. The method used in this research is quantitative research and distributing questionnaires to representative respondents, namely respondents who have used Wardah products and live in Purwokerto. This questionnaire technique uses a Likert scale and distributes the questionnaire online via Google Form. Because the population in this study is unknown. In this research, determining the sample size refers to Roscoe's research. The research method used is multiple linear regression analysis, with data processing carried out using IBM SPSS 26 Statistics. The research results show that Brand Awareness and Perceived Price have a positive influence on purchasing decisions, while Brand Association and Perceived Price have a negative influence on purchasing decisions.